Comparative study of voice onset time in English word-initial stop consonants produced by Uzbek and American speakers of English - Urazbaev, Khikmatullo; Sukhrobbekov, Sherzod (Penerbit Universiti Kebangsaan Malaysia, 2021)
The purpose of this study is to shed light on a comparative study of Voice Onset Time (VOT) values produced by Uzbek speakers of English and native speakers of American English. The study aimed to determine significant differences in terms of the VOT value in pronunciation of voiced and voiceless stop consonants in word-initial positions. Scholarly sources on the comparative study of Uzbek and English phonetics suggest that most of the Uzbek stop consonants possess similar qualities to those of English stop sounds (Abduazizov 1992; Yusupov 2013). A descriptive comparison of Uzbek and English consonants demonstrates the difference between the two languages in isolated forms rather than in speech. This study is motivated by the fact that little is known about recent studies on the instrumental comparative study of English plosives produced by Uzbek speakers of American English. In addition, so far, no studies have been carried out in VOT analysis of English sounds produced by Uzbek speakers. The research was conducted through voice recording and analyses of data collected from Uzbek speakers and American native speakers. Recordings of 3240 overall tokens were collected and analyzed using Praat phonetic software. The mean VOT values obtained from both subject groups have been compared and statistically tested using the Independent Samples t-test. The research findings show that Uzbek subjects’ and American native subjects’ VOT values differ significantly. However, there are a few words (9 out of 52) where the differences in the VOT values of the two subject groups are not statistically significant. The research presents implications for teaching pronunciation of English plosive sounds in word-initial positions where a stop consonant followed by a vowel sound to Uzbek speakers of English by taking into account the periodic measurement of consonants. In addition, there are implications for future research that might explore other features of VOT produced by Uzbek language speakers.